3D simulation of ion ribbon beam self-consistent dynamics in electrostatic undulator linac - Masunov, E.S.; Polozov, S.M.; Roshal, A.S.; Vinogradov, N.E. (Вопросы атомной науки и техники, 2001)
The ribbon ion beam focusing and acceleration in a periodical resonant system are considered by numerical simulation. The nonsynchronous RF field and electrostatic undulator field space harmonics exist in the structure. The dependence of beam output characteristics on electric field distribution and system parameters are investigated. Optimization of accelerator parameters in order to maximize transmission coefficient is carried out. The limit beam current is estimated. It is shown that high values of transmission and output currents in the linac under discussion can be obtained. The comparison with the results of early self-consistent 2D ion beam dynamics studies is done.